Theme and voice in poetry - Lamichhane, Sushil (Sahayaatra सहयात्रा, 2022)
Poetry is an ancient form of literature with musical qualities. A reader should go through the language structure, figures of speech and theme to explicitly analyze the poem. This article tries to define the theme and voice in a poem and explores the role of theme and voice in analyzing poetry. Analytical and descriptive research design has been applied to conclude. Identifying the theme and voice of poetry help to analyze poetry smoothly.